The Body of Fertility and the Body of Labor: The Evolution of Protection Policy for Female Workers in the"Four Periods"(1951-) - Wu, Ying (International Journal of Social Sciences and Public Administration, 2025)
China has now fully implemented the three-child policy. Women's reproduction is both the continuation of a family and the cultivation of new citizens for the nation and new labor power for society. Providing compensation for women's reproductive labor has become a consensus. However, with the opening of the three-child policy, the labor women undertake in reproduction-from pregnancy and childbirth to childcare, education, and ultimately nurturing qualified labor-requires increased energy and costs. How to reasonably distribute this increased burden has become a new social issue. This paper traces the evolution of the Chinese Communist Party's (CCP) policies concerning the "Four-Period" protection (pregnancy, postpartum, lactation, and menstruation periods) for female workers from 1951 to the present. Seeking to understand the epistemological foundation of this protection, the paper traces back to the founding of the CCP, exploring the initial ideological basis for constructing the "Four-Period" protection policy. Starting from the historical origins of the policies, it analyzes the underlying concepts behind the institutional design in different periods, the continuity and changes in the policy content itself, and the social practice of "Four-Period" protection at each stage. Thus, it presents the complete process of the construction and evolution of "Four-Period" protection over a long historical span, further exploring the discourse and changes in the social status of modern Chinese women. Re-integrating and re-distributing the responsibilities of the state, market, family, and individuals in the sphere of reproduction remains a crucial issue to be addressed. This paper aims to historically analyze the design philosophy behind the CCP's "Four-Period" protection system for women, the evolution of the system itself, and its practice, exploring the changing relationship between Chinese female workers, enterprises, and the state over the past century. It hopes to provide a long-term historical perspective and potential lessons for the formulation of current women's labor protection policies.